Explaining Experiences, Challenges and Adaptation Strategies in COVID-19 Patients: A Qualitative Study in Iran - Sina Ahmadi; Sina Ahmadi; Seyed Fahim Irandoost; Ahmad Ahmadi; Javad Yoosefi Lebni; Mohammad Ali Mohammadi Gharehghani; Nafe Baba Safari (Frontiers Media S.A., 2022)
ObjectiveGetting COVID-19 makes a person confront numerous individual, physical, psychological, family and social challenges. Therefore, the present study was conducted to explain the experiences, challenges and adaptation strategies in patients with COVID-19 in Tehran, Iran.MethodsThe present study was performed with a qualitative approach and phenomenological method among 33 patients with COVID-19. From July 20 to September 21, access to participants and data collection were done in person (15 people) and by phone (18 people) through targeted sampling and snowball and semi-structured interviews. Data management was carried out using MAXQDA-2018 software and its analysis was done by the Colaizzi analysis method. Guba and Lincoln's criteria were also observed to improve the quality of results.ResultsAfter analyzing the data, two main categories and 17 subcategories were obtained, including (1) experiences and challenges (ignoring the disease, blaming, physical health disorders, mental problems, guilt, and remorse, being blamed, living a life of disappointment and ambiguity, emotional challenges, frustrating reactions from others, helplessness and limitation) and (2) disease adaptation strategies (spirituality, learning about COVID-19, doing valuable and fun activities, participating in treatment, strengthening one's spirit and hope, trying to make up for past mistakes and virtual communication).ConclusionsBased on the results, interventions and policies such as increasing people's health knowledge and literacy to get acquainted with the symptoms of the disease and prompt referral for diagnosis and treatment, teaching stress and psychological pressure management techniques, instructing families to continue emotional and social support for patients and strengthening and reproducing the strategies patients use, along with teaching disease coping skills, harnessing the potential of cyberspace and the media can make it easier to tolerate illness and get back to life.